Economic Growth, Economic Reform anf Rising Inequality in China. - Knight, J; Song, L (Department of Economics (University of Oxford), 1999)
The paper analyses two cross-section national household surveys, relating to the years 1988 and 1995, to explain the rise in inequality of income that occured in Chine over those seven years. The Gini coefficient of household income per capita increased from 38 to 45 per cent, i.e. by 1,0 percentage points per annum. Owing to the sharp institutional and economic devide betweeen rural and urban China, the rural and urban samples are analysed separately. The two main explanations for the rise in inequality are economic growth and economic transition.